2021
DOI: 10.1093/plphys/kiab323
|View full text |Cite
|
Sign up to set email alerts
|

CALMODULIN-LIKE-38 and PEP1 RECEPTOR 2 integrate nitrate and brassinosteroid signals to regulate root growth

Abstract: Plants exhibit remarkable developmental plasticity, enabling them to adapt to adverse environmental conditions such as low nitrogen (N) in the soil. Brassinosteroids (BRs) promote root foraging for nutrients under mild N deficiency, but the crosstalk between the BR- and N-signaling pathways in the regulation of root growth remains largely unknown. Here, we show that CALMODULIN-LIKE-38 (CML38), a calmodulin-like protein, specifically interacts with the PEP1 RECEPTOR 2 (PEPR2), and negatively regulates root elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Different NO 3 − concentrations can either inhibit or stimulate primary root elongation ( 3 , 5 , 30 33 ). To further identify NO 3 − -related regulators of root growth, we performed a forward genetic screen to look for Arabidopsis mutants that were less sensitive to low NO 3 − when grown on medium containing 0.05 mM NO 3 − .…”
Section: Resultsmentioning
confidence: 99%
“…Different NO 3 − concentrations can either inhibit or stimulate primary root elongation ( 3 , 5 , 30 33 ). To further identify NO 3 − -related regulators of root growth, we performed a forward genetic screen to look for Arabidopsis mutants that were less sensitive to low NO 3 − when grown on medium containing 0.05 mM NO 3 − .…”
Section: Resultsmentioning
confidence: 99%
“…CML37 is a positive regulator of herbivory-induced defense, and mutation of CML37 decreases the JA level in Arabidopsis ( Scholz et al 2014 ). CML38 can interact with the PEP1 RECEPTOR 2, a receptor for the DAMP plant elicitor peptide (Pep) 1 and Pep2, to regulate root development in Arabidopsis ( Song et al 2021 ). Therefore, it is possible that esDNA regulates calcium signaling to modulate JA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment of proscoop12 mutant roots with synthesized PROSCOOP12 peptide inhibited the elongation of roots by reducing the number of meristematic cells and cell length (Guillou et al., 2022). Recently, it has been reported that CALMODULIN‐LIKE‐38 (CML38) was induced by low nitrate conditions, and the cml38 mutant shows longer root length in A. thaliana (Song et al., 2021). Unlike DEFL202 and DEFL203, CML38 negatively regulates nitrate uptake.…”
Section: Discussionmentioning
confidence: 99%